At the Basis of Brain Malformations: Brain Plasticity, Developmental Neurobiology, and Considerations for Rehabilitation - Praticò, Andrea D.; Leotta, Michela; Cavallaro, Paola; Sciuto, Laura; Vecchio, Michele; Di Napoli, Claudia; Polizzi, Agata; Ruggieri, Martino (Journal of Pediatric Neurology, 2024)
From early age in the human brain occurs plasticity process that influences its development. The functioning of the brain is governed by its neuronal connectivity and the synaptic dynamics of these connections. A neuron, over thousands of synapses, can receive a large number of inputs and produce different outputs leading to the consolidation and integration of memory. Synaptic plasticity is the set of experience-dependent changes in neuronal pathways that support acquired habits. It is the ability of the nervous system to reshape connectivity between neurons, changing the functional and structural organization of neuronal circuits that allows us to adapt to the multiple and continuous changes in the environment and leading to processes such as cognitive development and the ability to learn. Synaptic plasticity is mainly due to short- and long-term mechanisms. Short-term synaptic plasticity refers to changes in synaptic strength that occurs very quickly (from one-thousandth of a second to 5 minutes) and are temporary and decay over minutes (maximum 30 minutes). Long-term synaptic plasticity is defined by a long-lasting, activity-dependent change in synaptic efficacy, last from hours up to a lifetime (from 30 minutes to weeks, months, and years) and is thought to constitute the basis of learning and memory. A significant difference occurs in the nature of the change; short-term plasticity adds only a functional change, whereas long-term plasticity causes not only functional but also structural changes. Aside from genetic factors and metabolic processes, brain development is mediated also by environmental factors. Interaction with the environment plays a key role in the development and growth of neural networks and neuroplasticity. Environmental interactions that can modify and increase the development of neural networks and intelligence in children are several and are herein discussed.
Keywords: developmental neurobiology; synapses; environmental factors